Innovation of Project-Based Learning Model to Support Students' Digital Literacy Abilities: A Literature Review - Maulida, Husna; Ani Rakhmawati (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Digital literacy is one of the main competencies that need to be developed in 21st century education. In an effort to improve students' digital literacy, a Project Based Learning (PjBL) based learning model emerges as an innovative alternative that encourages active involvement of students in the learning process. This article presents a literature review on the effectiveness of PjBL in supporting digital literacy, with a focus on developing critical thinking, collaboration, communication, and creativity skills. Based on the review of various literature sources, PjBL not only improves learners' understanding of learning materials, but also provides relevant and applicable learning experiences in the context of digital technology. PjBL allows learners to explore, use and create digital content, thus improving digital literacy skills holistically. However, the implementation of PjBL in digital literacy learning still faces challenges, especially in terms of infrastructure, educator training and policy support. This study recommends more comprehensive support from various parties so that the PjBL learning model can be effectively implemented in various educational environments. Thus, PjBL has the potential to be an adaptive and innovative strategy in facing digital literacy challenges in students.